DAMPAK PENGOPERASIAN FEEDER WIRA-WIRI TERHADAP PERUBAHAN SOSIAL MASYARAKAT KOTA SURABAYA - Nurul Muchlisa; Rahmanu Wijaya (Universitas Negeri Surabaya (Unesa), 2024)
Wira-wiri Suroboyo is feeder-based public transportation operated by the Surabaya City Government to overcome various problems related to public transportation faced by Surabaya City residents. The aim of this research is to determine the impact of the operation of the Wira-wiri Suroboyo feeder on the people of Surabaya City. Data collection techniques in this research used interviews, observation and documentation. The research subjects were the Surabaya City Community and the Suroboyo Wira-wiri Crew. Data analysis in this research refers to interactive data as stated by Miles & Huberman, namely that it is carried out interactively continuously until complete so that accurate and definite data is obtained. From the results of research conducted by researchers, it can be concluded that the operation of the Wira-wiri Suroboyo feeder has had an impact on social change in the people of Surabaya City, such as the impact felt by non-users such as city transport drivers who are no longer operating, namely creating jobs, increasing income, getting used to obey the rules, and get used to socializing or communicating well. Meanwhile, the impact on the user community is making it easier to get public transportation, facilitating people's mobility or traveling from one place to another, getting people used to obeying the rules, and increasing social awareness.